(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
In Positron Emission Tomography (PET), phantoms are filled with liquid radioactive solutions for quality assurance (QA), and scanner characterization. The radioisotope 89Zr (half-life T1/2=78.4 hours) is used for immunoPET; due to its metallic nature it tends to deposit on the phantom walls [1], resulting in non-uniform distributions that are not suitable for QA. This fact also complicates cleaning and decontamination. Radioactive 3D printed phantoms have been proposed before, such as liquid resin mixed with 18F-fluorodeoxyglucose, the most widely used PET tracer (T1/2 =109.8 min) [2,3,4] or 68Ge (T1/2 =270 days) [5]. In this work, we 3D printed two radioactive phantoms containing 89Zr following the process described in [4], and studied their suitability for QA in PET, i.e., accumulation of 89Zr on the walls, or deviations from the desired homogeneity. The phantoms were a radioactive point source on a non-radioactive (cold) background, and a spherical source (1 cm3) within a cylindrical radioactive background (14 cm3) keeping an 8:1 sphere-to-background ratio. Both were scanned in the Inveon dedicated small animal PET (Siemens Healthineers) for 0.5 h and 4 h, respectively. The sphere was inspired by the QA phantom of the NEMA NU 2–2018 standards [6]. Additionally, a 15-mL syringe filled with the remaining radioactive resin was scanned for 5 min. The PET images of the point source revealed activity in the cold background which indicates that 89Zr deposited on the phantom walls during the print. In the sphere phantom, the radioisotope was not homogeneously distributed; however, the 8:1 ratio was observed in terms of the mean counts of each region. The analysis of the reconstructed images of the syringe showed that the 89Zr accumulated at its bottom and it was precipitating from the resin. This was confirmed by a second scan after a 90? rotation of the syringe. The sphere phantom was rescanned three weeks later, and no significant changes in the activity distribution were observed. This points out to the effectiveness of 3D printing in maintaining the spatial activity distribution within the phantom, preventing the adherence of 89Zr to the phantom walls. We believe that the formation of hot spots within the prints can be solved by continuously mixing the resin while printing. Therefore, future studies should include improving the mixing process. Author’s statement Authors state no conflict of interest. The work is partially supported by the German Research Foundation (DFG) under grant no. 496099829, the DFG Cluster of Excellence PMI under grant no. 390884018 and German Federal Ministry for the Environment, Nature, Conservation and Nuclear Safety under grant no. BMU 67KI2036C. References [1] M.-A. Park et al, Adsorption of metallic radionuclides on plastic phantom walls, Med. Phys., vol. 35, no. 4, pp. 1606-1610, 2008. [2] T. Läppchen et al, 3D printing of radioactive phantoms for nuclear medicine imaging, EJNMMI Physics, vol. 7, no. 1, Apr. 2020. [3] J. I. Gear et al, Radioactive 3d printing for the production of molecular imaging phantoms, Phys, Med. Biol., vol. 65, no. 17, Sep. 2020. [4] S. Seeger et al, 3D printed radioactive phantoms for positron emission tomography, Trans. AMMM, vol. 4, no. S1, p. 640, Sep. 2022. [5] L. P. Meier et al, 3D printing of calibrated Germanium-68 PET phantoms without inactive walls IEEE TRPMS, vol. 2023, pp. 1-1, 2023. [6] NEMA standards publication NU 2-2018: Performance measurements of positron emission tomographs (PET).